1999
DOI: 10.21273/hortsci.34.4.669
|View full text |Cite
|
Sign up to set email alerts
|

Preplant Lime and Micronutrient Amendments to Pine Bark Affect Growth of Seedlings of Nine Container-grown Tree Species

Abstract: The objective of this study was to determine the effects of lime and micronutrient amendments on growth of seedlings of nine container-grown landscape tree species in two pine bark substrates with different pHs. Acer palmatum Thunb. (Japanese maple), Acer saccharum Marsh. (sugar maple), Cercis canadensis L. (redbud), Cornus florida L. (flowering dogwood), Cornus kousa H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 8 publications
2
13
0
2
Order By: Relevance
“…2 and 3. This fi nding is consistent with research by Wright et al (1999a) who reported that increasing pine bark substrate pH by liming reduced growth of nine container-grown landscape tree species as well as PB solution Fe, Mn, Cu, and Zn concentrations. Micronutrient solution concentrations for both species were generally higher for Micromax than for all other treat-ments (Table 2).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…2 and 3. This fi nding is consistent with research by Wright et al (1999a) who reported that increasing pine bark substrate pH by liming reduced growth of nine container-grown landscape tree species as well as PB solution Fe, Mn, Cu, and Zn concentrations. Micronutrient solution concentrations for both species were generally higher for Micromax than for all other treat-ments (Table 2).…”
Section: Resultssupporting
confidence: 92%
“…Substrates of container-grown plants are commonly preplant amended with sulfated micronutrients with the intention of increasing the supply of micronutrients to the plant. Wright et al (1999a) showed that seedling growth of nine container-grown tree species in pine bark was positively affected by the addition of Micromax (Scotts-Sierra, Marysville, Ohio), a sulfated micronutrient fertilizer package. However, Kelk (2002), investigating the infl uence of CuSO 4 , FeSO 4 , MnSO 4 , and ZnSO 4 on the growth of Quercus palustris (Müench), found that growth was increased to the same degree as Micromax by amending pine bark with any three of the four sulfated micronutrients or by any one sulfated micronutrient in the absence of the other three.…”
mentioning
confidence: 99%
“…For the limed treatments, the increase in dry weights from the 0.0 rate to the rate at which maximum growth occurred was 54% and 80% for the FeSO 4 and MM treatments, respectively. These data are A pin oak Dry weight (g) consistent with the fi ndings of Wright et al (1999aWright et al ( , 1999b who observed that amending PB with lime reduced growth of nine container-grown tree species in a PB substrate. This growth reduction was attributed to reduced micronutrient availability at higher substrate pH.…”
Section: Resultssupporting
confidence: 89%
“…Esse fato evidencia a importância da aplicação de micronutrientes na adubação, quando produzidas mudas de pessegueiro-bravo. Wright et al (1999), em estudo de crescimento de nove espécies arbóreas, utilizando ou não calcário e micronutrientes em dois substratos de casca de Pinus taeda, com diferentes valores de pH, observaram uma maior BSPA e altura das plantas em todas as espécies em que foram utilizados micronutrientes.…”
Section: Discussionunclassified